Carotenoids from gac fruit aril (Momordica cochinchinensis [Lour.] Spreng.) are more bioaccessible than those from carrot root and tomato fruit. (September 2017) - Müller-Maatsch, Judith; Sprenger, Jasmin; Hempel, Judith; Kreiser, Florence; Carle, Reinhold; Schweiggert, Ralf M.
Abstract: Using a simulated digestion procedure in vitro, liberation and bioaccessibility of β-carotene (29.5 ± 1.7% and 22.6 ± 0.9%, respectively) and lycopene (51.3 ± 2.6% and 33.2 ± 3.1%, respectively) from gac fruit aril were found to be significantly higher than from carrot root (β-carotene, 5.2 ± 0.5% and 0.5 ± 0.2%, respectively) and tomato fruit (lycopene, 15.9 ± 2.8% and 1.8 ± 0.5%, respectively). Gac fruit aril naturally contained significantly more lipids (11% on fresh weight base) than carrot root and tomato fruit (< 1%). However, when test meals were supplemented with an O/W emulsion to match the content of gac fruit aril, carotenoid bioaccessibility was still considerably lower than that from genuine gac fruit aril. Carotenoids in gac fruit aril were found to be stored in small, round-shaped chromoplasts. Despite the high lipid content, these carotenoids are unlikely to occur in a lipid-dissolved state according to simple solubility estimations, instead being possibly deposited as submicroscopic crystallites. In contrast, carotenoids of carrot root and tomato fruit were stored in large, needle-like crystallous chromoplasts. Consequently, we hypothesized the natural deposition form to be majorly responsible for the observed differences in bioaccessibility. A favorable surface-to-volume ratio of the deposition form in gac fruit aril might have allowed a more rapid micellization during digestion, and thus, an enhanced bioaccessibility. Irrespective of the ultimate reason, gac fruit aril provided a highly bioaccessible form of both lycopene and provitamin A (β-carotene), thus offering a most valuable dietary source of both carotenoids. Currently, gac is majorly grown in Southeast Asia, where its consumption might help to diminish the 'hidden hunger' namely the insufficient supply with vitamin A. Ultimately, gac fruit might thus contribute to alleviating most severe health implications of vitamin A deficiency, such as anaemia and xerophthalmia, the prevailing cause of preventable childhood blindness, as well as mortality from infectious diseases. Graphical abstract: Highlights: Gac aril exhibits exceptionably high liberation & bioaccessibility of carotenoids. Bioaccessibility was significantly higher from gac than from carrot and tomato. Carotenoids of gac aril are deposited in a non-lipid-dissolved, yet unknown form. Chromoplastidal substructure might have influenced bioaccessibility. Overcoming vitamin A deficiencies, gac fruit might be a valuable dietary component.